The Encyclopedia of philosophy - Edwards, Paul (Macmillan & The Free Press ; Collier-Macmillan, 1967)
Treats eastern & western philosophy; it deals with ancient, medieval and modern philosophy; and it discusses the theories of mathematicians, physicist, biologist, sociologists, psychologists, moral reformers and religious thinkers where these have had an impact on philosophy.